The Model of Developing Arabic Language Skills at Daarul Ukhuwwah Islamic Boarding School Malang - Boby Ghufron; Nurhadi Nurhadi; Syaiful Mustofa; Moch. Fikri Abdul Aziz (Universitas Ahmad Dahlan, 2023)
The success of learning Arabic in Islamic boarding school can be measured by the number of students who are able to speak Arabic and have four Arabic skills. The learning model in Daarul Ukhuwwah Islamic boarding school is seen as effective in developing students' language skills. Therefore, it is necessary to carry out research related to the development model of Arabic language learning in Daarul Ukhuwwah Islamic boarding school. The purpose of this research is to determine the model of developing Arabic language skills in Daarul Ukhuwwah Islamic boarding school. The method used is a descriptive qualitative method. The research data includes primary data in the form of core data from the research location, and secondary data in the form of documentation. Research data collection techniques use observation, interviews, and documentation. The process of analyzing research data includes data reduction, data presentation, and conclusion making. The results showed that Daarul Ukhuwwah Islamic boarding school uses the imigram model in designing and implementing language agendas that are useful for developing the four Arabic language skills of its students. The model seeks to provide a balance between Arabic practice and theory. This research can be used as an example of an innovative model of developing Arabic language skills.